Urban Fruit Quality Traceability Model Based on Smart Contract for Internet of Things. (15th August 2021) - Xu, Cheng; Chen, Kai; Zuo, Min; Liu, Hongzhe; Wu, Yanan
Abstract : In Internet of things, compared with the traditional traceability system, the existing system has difficulties in operation, data are easily lost, data are uncoordinated, standards are not unified, and so on. In this paper, based on the characteristics of blockchain, the traceability model of urban fruits is established to reduce the risk of counterfeit and shoddy urban fruits. The collected data is integrated into the chain for diversified display, providing different permissions and platforms for multiple roles. Blockchain and supporting intelligent hardware are used to realize the real record and tracking of the whole process of fruit. Improve the transparency and efficiency of supply chain, and reduce the supply chain cost. The experimental results show that the proposed algorithm model can be applied to the fruit service field and effectively improve the service level of smart city.